COMPARATIVE STUDY ON OVA RECOVERY IN Bos indicus AND Bos taurus CATTLE: A SYSTEMATIC ANALYSIS STUDY - Siti Darodjah Rasad; Nena Hilmia; Sari Suryanah; Cece Sumantri; Irma Irma (BIOTROPIA, 2025)
HIGHLIGHTS- Domestic cattle sub species of Bos indicus shows higher ova in their reproduction than Bos taurus- In vitro techniques produce higher ova recovery than in vivo techniques.- Dairy cattle showed higher ova recovery than in beef cattle or dual-purpose cattleABSTRACTEmbryo transfer biotechnology has long been applied and is massively used to increase female cattle's reproductive ability. This biotechnology is done with the hope of increasing livestock productivity. Extensive research has been carried out and the responses of each breed of cattle shows varied. This research was conducted to determine whether the cattle breed influences the oocyte and embryo recovery rate in the embryo transfer process. A meta-analysis study was conducted on published research regarding the potential for ova recovery of Bos taurus and Bos indicus. Screening process resulted 14 publications with 21 studies were obtained which could be analyzed further. Cattle breed influence on ova recovered indicated by Standardize Mean Difference (SMD) 0.72 ± 0.206, 95% CI: 0.32–1.11. The heterogeneity test showed that there was a difference between studies (I2 = 89.99, p<0.01). The effect size classification shows in medium category. Based on moderator variable analyses, Bos indicus showed a higher potential for ova recovery than Bos taurus with in vitro techniques. Sub-group analysis of cattle types showed that the difference in ova between the two breeds was significant in the dairy type (p<0.01), while there was no difference in the dual-purpose vs. dairy.